Detection and Prevalence of Soil Transmitted Helminths Contaminating Several Vegetables in Several Traditional Markets in Surabaya - Yuhenanda Dary Pratama; Indah Setyawati Tantular; Gwenny Ichsan Prabowo; Heru Prasetya (Journal of Parasite Science, 2023)
A total of 100 fresh vegetable samples consisting of yardlong bean, cabbage, lettuce, and lemon basil were purchased from five traditional markets in Surabaya. Each sample was washed with tap water, water washing examined using flotation method to find soil-transmitted helminths. The overall prevalence of soil-transmitted helminths contamination was 41% (41/100). The most predominant parasite was hookworms (20%), followed by Strongyloides stercoralis larvae (14%) and Ascaris lumbricoides eggs (7%). The highest prevalence of contamination was found in lettuce, with a prevalence rate of 56% (14/25), while the lowest prevalence of contamination was found in yardlong bean, with a prevalence rate of 24% (6/25). Sequentially, the prevalence of soil-transmitted helminths contamination of fresh vegetable samples from Pabean traditional market (55%), Keputran traditional market (50%), Wonokromo traditional market (50%), Lakarsantri traditional market (35%) and Mulyosari traditional market (15%), respectively. The present study demonstrated that consumption of vegetables with parasite contamination in this area represents a potential route for the transmission of soil-transmitted helminths infection.